Improvements on the cross-correlation algorithm used for tracking fractional Bragg grating wavelength shifts in multimode fibres - Theodosiou, Antreas; Komodromos, Michael; Kalli, Kyriacos (My University, 2018)
In this paper we report on the deployment of Finite Impulse Response (FIR) filters as an extension to the common cross-correlation algorithm (CCA), for accurate peak tracking of multimode and single mode fibre Bragg gratings when dealing with wavelength shifts below the sampling resolution of the demodulator; the well-known peak-locking effect. The performance of the common CCA under these conditions was studied using simulations for single and multiple peak grating spectra and was compared with the performance of proposed, improved CCA method. We studied the cases where fibre Bragg gratings are wavelength-shifted with triangular and sinusoidal manner and how the proposed method behaves under these conditions. We experimentally evaluated our proposed method by utilising strain measurements using a fibre Bragg grating inscribed in a multimode gradient index CYTOP polymer fibre. The method and algorithm showed significant improvement concerning the peak-locking effect, while maintaining the response speed.
Keywords: Bragg grating sensors; Cross-correlation; Demodulation algorithm; Optical fibre sensors; Smoothing filter